Effect of postural changes on 3D joint angular velocity during starting block phase - Slawinski, J.; Dumas, R.; Cheze, L.; Ontanon, G.; Miller, C.; Mazure-Bonnefoy, A. (Journal of Sports Sciences, 2013)
Few studies have focused on the effect of posture during sprint start. The aim of this study was to measure the effect of the modification of horizontal distance between the blocks during sprint start on three dimensional (3D) joint angular velocity. Nine trained sprinters started using three different starting positions (bunched, medium and elongated). They were equipped with 63 passive reflective markers, and an opto-electronic Motion Analysis® system was used to collect the 3D marker trajectories. During the pushing phase on the blocks, norm of the joint angular velocity (NJAV), 3D Euler angular velocity (EAV) and pushing time on the blocks were calculated. The results demonstrated that the decrease of the block spacing induces an opposite effect on the angular velocity of joints of the lower and the upper limbs. The NJAV of the upper limbs is greater in the bunched start, whereas the NJAV of the lower limbs is smaller. The modifications of NJAV were due to a combination of the movement of the joints in the different degrees of freedom. The medium start seems to be the best compromise because it leads, in a short pushing time, to a combination of optimal joint velocities for upper and lower segments.